Assessment of Farmers Knowledge Level on Turmeric Cultivation Practices - , Dhivya C, Arunkumar R, Muthukumar R (Archives of Current Research International, 2024)
Turmeric (Curcuma longa), one of the oldest known medicinal plants, has been used for centuries due to its significant health benefits. Curcumin, the primary bioactive compound found in turmeric, belongs to the Zingiberaceae family and is well-documented for its antibacterial, antifungal, renal, and hepatoprotective properties. This study was conducted in the Kodumudi block of Erode District, Tamil Nadu, due to its extensive turmeric cultivation. A sample of 120 farmers was selected to assess their knowledge of recommended turmeric cultivation technologies. The results indicated that the turmeric growers possessed a medium level of knowledge regarding the recommended practices for turmeric cultivation. The research employed an analytical approach to assess farmers' understanding of key practices including main field preparation, planting techniques, nutrient management, and pest and disease control. The findings reveal that while growers displayed strong knowledge in areas such as seasonal practices, irrigation, and spacing, there were significant gaps in their understanding of rhizome treatment, micronutrient application, and pest management. Specifically, knowledge about managing pests such as rhizome scales, leaf rollers, and shoot and root borers was notably lacking. The study highlights the need for targeted training and educational programs to address these gaps, particularly in pest identification and control measures. By enhancing farmers' knowledge in these critical areas, the study aims to improve turmeric cultivation practices and contribute to the sustainability of turmeric farming in Erode District.